Low glucose induces mitochondrial reactive oxygen species via fatty acid oxidation in bovine aortic endothelial cells. Issue 6 (24th May 2017) - Kajihara, Nobuhiro; Kukidome, Daisuke; Sada, Kiminori; Motoshima, Hiroyuki; Furukawa, Noboru; Matsumura, Takeshi; Nishikawa, Takeshi; Araki, Eiichi
Abstract: Aims/Introduction: Overproduction of reactive oxygen species (ROS) in endothelial cells (ECs) plays a pivotal role in endothelial dysfunction. Mitochondrial ROS (mtROS) is one of the key players in the pathogenesis of diabetic vascular complications. Hypoglycemia is linked to increased ROS production and vascular events; however, the underlying mechanisms remain unclear. In the present study, we aimed to determine whether and how low glucose (LG) mediates mtROS generation in ECs, and to examine the impact of LG‐induced mtROS on endothelial dysfunction. Materials and Methods: Metabolomic profiling, cellular oxygen consumption rate, mtROS, endothelial nitric oxide synthase phosphorylation, and the expression of vascular cell adhesion molecule‐1 or intercellular adhesion molecule‐1 were evaluated in bovine aortic ECs. Results: We found that LG increased mtROS generation in ECs; which was suppressed by overexpression of manganese superoxide dismutase. Comprehensive metabolic analysis using capillary electrophoresis‐mass spectrometry and oxygen consumption rate assessment showed that the pathway from fatty acid to acetyl‐CoA through fatty acid oxidation was upregulated in ECs under LG conditions. In addition, etomoxir, a specific inhibitor of the free fatty acid transporter, decreased LG‐induced mtROS production. These results suggested that LG increased mtROS generation through activation of fatty acid oxidation. We further revealed that LG inhibited endothelial nitric oxide synthase phosphorylation, and increased the expression of vascular cell adhesion molecule‐1 and intercellular adhesion molecule‐1. These effects were suppressed either by overexpression of manganese superoxide dismutase or by treatment with etomoxir. Conclusions: The activation of fatty acid oxidation followed by mtROS production could be one of the causes for endothelial dysfunction during hypoglycemia. Abstract : Low glucose (LG) conditions increase mitochondrial reactive oxygen species (ROS) generation through enhanced fatty acid oxidation in endothelial cells. LG conditions decrease the phosphorylation of eNOS and increase the expression of VCAM‐1 and ICAM‐1, which wewe suppressed by either overexpression of MnSOD or etomoxir, a CPT1 inhibitor.